2021
DOI: 10.1142/s0219686722500202
|View full text |Cite
|
Sign up to set email alerts
|

Examination and Optimization of Machining Parameters in Electrical Discharge Machining of UNS T30407 Steel

Abstract: Electrical discharge machining (EDM) is a non-conventional process utilized for machining electrically conductive materials which cannot be machined by conventional processes. This paper is focused on modeling and optimization in electrical discharge machining (EDM) of UNS T30407 steel. The variables such as pulse on time (Ton), pulse off time (Toff), and current will influence the material removal rate (MRR) and surface roughness (Ra) which were taken as response variables. Experimental data were collected as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In micro EDM, the small pulse energy is one of the prominent research topics. The major discharge energy generation methods are the relaxation pulse generator [8] and the transistor-pulse generator [9]. Singh et al [8] verified that the relaxation pulse generator can generate low discharge energy by charging and discharging the capacitor adopted in the main power loop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In micro EDM, the small pulse energy is one of the prominent research topics. The major discharge energy generation methods are the relaxation pulse generator [8] and the transistor-pulse generator [9]. Singh et al [8] verified that the relaxation pulse generator can generate low discharge energy by charging and discharging the capacitor adopted in the main power loop.…”
Section: Introductionmentioning
confidence: 99%
“…The major discharge energy generation methods are the relaxation pulse generator [8] and the transistor-pulse generator [9]. Singh et al [8] verified that the relaxation pulse generator can generate low discharge energy by charging and discharging the capacitor adopted in the main power loop. Ichikawa and Natsu [10] further confirmed that the existing stray capacitance in the machine tool limited its access to the minimal discharge energy with a short duration and high frequency, even if removing the capacitors in the main power loop.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Raj A et al used graphene nanoplates to improve the machinability of Inconel 718 with graphene in two forms: as a solid lubricant and as an inclusion in the cutting fluid; the performance was compared by measuring cutting forces, cutting temperatures, tool wear and surface roughness, and the results showed that both forms of graphene exhibited superior performance to dry machining [6].Singh P et al experts prepared Al-4032 based composites with SiC mass fraction of 6% by stir casting apparatus and tested the composites for tensile strength, micro hardness and impact strength. Cutting speed, feed rate and depth of cut were the cutting parameters selected to check the response surface finish and energy consumption and the results showed that the expectation value approach based on response surface methodology was used to obtain the desired goal of achieving optimal combination of parameters [7]. It was found that there is relatively little research into machining applications based on 3D technology.…”
Section: Introductionmentioning
confidence: 99%